DAMPAK MEA TERHADAP INVESTASI, EKSPOR-IMPOR DAN PENGGUNAAN TENAGA KERJA INDONESIA - Khasanah, Nur; Astuti, Prihartini Budi; Kristanti, Ika Neni (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
This research attempts to analyze the effects of the economic integration of the ASEAN Economic Community (AEC) which was implemented since 2015. The impact analyzed is focused on investments made in Indonesia, both investments made by foreign investors and domestic investors. Another thing that was also highlighted in this study was the flow of exports and imports. This was also investigated because one of the policies contained in the agreement of the ASEAN economic community was the elimination of international trade barriers. In addition to the two things above, researchers also analyzed the influence of the ASEAN economic community on the use oflabor in Indonesia. The data analyzed in this study are secondary data obtained from the relevant agencies. The method used in this study is a different sample pair test. This method is used because the research conducted is comparing the conditions of investment, export-import and use of labor in Indonesia before and after the economic integration of the ASEAN Economic Community. At the end of this study, researchers will provide recommendations to the government regarding what should be done by the government to optimize investment activities, exports and use of local labor in Indonesia.